God in the brain: Experiencing psychosis in the postsecular United States. (August 2016) - Jones, Nev; Kelly, Timothy; Shattell, Mona
There is a growing literature on what contemporary cultural theorists have broadly termed the "postsecular": the abandonment of clear-cut boundaries between the secular and nonsecular in the industrialized West and an embrace of a complex understanding of what is real that neither accepts nor rejects the supernatural. These new cultural currents may affect not only philosophers and theologians, but also the ways in which individuals with psychosis make sense of their experiences. This paper reports on the key findings of an in-depth qualitative analysis of 19 interviews of individuals diagnosed with psychotic disorders. The majority of participants described ongoing and self-conscious struggles to demarcate their experiences as the products of the real world or a "crazy" mind. With equal frequency, participants weighed and debated competing secular and supernatural explanations, often juxtaposing and blending different explanatory frameworks. We found that this syncretic process affected not only the content of psychotic experiences—what delusions or hallucinations are about—but also the type of arguments or logics used to justify particular interpretations. We discuss the implications of these observations with respect to clinical practice and the broader phenomenology of psychosis, challenging often oversimplified discourse on "insight" and suggesting that polarization(s) between "biomedical" and "psychosocial" explanations may be of less relevance to patients' real-world experiences than is often assumed.